ETIKA PROFESI HAKIM - Suharsono; Zaim, Mahibu; Tua, Hafizd Purbala; Jamaludin, Nurrun (al-Rasῑkh: Jurnal Hukum Islam, 2023)
Discourses about professional ethics of judges started out from the reality of law enforcement officials (especially judges) that ignore the values of morality. Although judges have already had the professional code of ethics as moral standards it has not yet brought positive impact on negative image in public view. One way to enforce the rule of law is to urge ethics, professionalism, and discipline. Professional ethics of judges contain moral values underlying professional personality, namely freedom, fairness and honesty. Professional ethics of judges and law are a unity that is inherently contained ethical values of Islam which is the foundation of understanding the Qur’an, so basically the code of professional conduct of judges is in line with the values of the Islamic ethical system. Ethics Islamic law is built on four basic values, namely the values of truth, justice, free will and responsibility